Influences of Reciprocal Altruistic Preferences and Reference Low-Carbon-Level Effect on Carbon Emission Transfer Strategies of Supply Chains - Biying Zhao; Dongyue Li; Licheng Sun; Wentao Wang (Mathematics)
Consumers’ low-carbon preferences will affect the decision-making behavior of supply chain members; an understanding of the influence mechanism of reciprocal altruistic preferences and reference low-carbon-level effect on carbon emission transfers in a supply chain is of great significance for optimizing transfer and reducing emissions and enhancing the overall emission reduction effect of the supply chain. By constructing a manufacturer-led differential game model, we analyzed the carbon emission transfer strategy of a supply chain under the influence of the reference low-carbon level effect and reciprocal altruistic preferences in scenarios with and without such preferences. The results showed that the reference low-carbon-level effect had a positive influence on the manufacturer’s transfers but not on the supplier’s acceptance of them. Moreover, reciprocal altruistic preferences increased both the transfer and acceptance of emissions while improving the low-carbon level of products. Under the influence of reciprocal preferences, the difference in the degree of altruism will also affect the carbon emission transfer and acceptance behavior of the manufacturer and supplier. When the supplier’s reciprocal altruism coefficient and the consumer’s memory parameter remain within a certain range, the transfers positively affect cooperation in the supply chain.